AN EXPERIMENTAL MODEL FOR ASSESSING THE LEVEL OF DIGITIZATION IN BEEKEEPING - Tsvetan TSVETANOV; Krasimir DIMOV; Evgeni PETKOV (Scientific Papers Series : Management, Economic Engineering in Agriculture and Rural Development)
A mathematical model has been developed to assess the digitization of the beekeeping sector. For this purpose, the summarized results of questionnaire surveys of 37 apiaries located in the regions of Plovdiv and Pleven municipalities in Bulgaria were used. For evaluation on the degree of digitization of the apiaries we took under consideration only what software and hardware products are used. The results showed a low degree of digitization of the studied apiaries - in 27 out of 37 studied apiaries there were no data about the use of software and hardware applications, and the average level of digitization for the studied apiaries according to the model we developed was within 8-9 %. A survey on the awareness of those employed in the beekeeping about some basic digital products for collecting, storing and distributing information and their willingness to use them in the future was also conducted. It was found that between 21% and 35% of the respondents were not familiar with the basic digital products. Far more worrying was that between 50 % and 70% of respondents stated that they were familiar with the listed digital products, but did not intend to use them in the near future.